Lung cancer in patients with Idiopathic Pulmonary Fibrosis. A retrospective multicenter study in Greece. (February 2020) - Tzouvelekis, Argyris; Karampitsakos, Theodoros; Gomatou, Georgia; Bouros, Evangelos; Tzilas, Vassilios; Manali, Efrossyni; Tomos, Ioannis; Trachalaki, Athina; Kolilekas, Lykourgos; Korbila, Ioanna; Tomos, Periklis; Chrysikos, Serafeim; et al.
Abstract: Background: Abundant evidence supports an association between Idiopathic Pulmonary Fibrosis (IPF) and lung cancer development. Data on diagnosis and management of patients with IPF and lung cancer are still scarce. Patients and methods: This was a retrospective multicenter study, enrolling 1016 patients with IPF from eight different centers between 2011 and 2018 in Greece. Our aim was to estimate prevalence of lung cancer in patients with IPF in Greece. Results: We identified 102 cases of patients with IPF and lung cancer (prevalence = 10.03% n = 102/1016, mean age±SD = 71.8 ± 6.9, 96 males, mean FVC±SD = 72.7 ± 19.7, mean DLCO±SD = 44.5 ± 16.3). We identified 85 cases (83.3%) of non-small cell lung cancer (35 squamous, 28 adenocarcinoma), and 15 cases (14.7%) of small cell lung cancer. Primary lesion was localized in lower lobes in 57.1% of cases. Lung cancer was diagnosed post IPF diagnosis (mean latency time + SD = 33.2 + 36.1 months) in 57.6% of patients and synchronously in 36.5% of patients. Chemotherapy was applied in 26.7% of cases, while 34.7% of patients underwent surgery. Median survival of patients with IPF and lung cancer was 27.4 months (95% CI: 20.6 to 36.8). Conclusions: IPF is a risk factor for lung cancer development. In line with current literature, squamous cell carcinoma is the most common histologic subtype in patients with IPF. Large randomized controlled studies on the management of patients with IPF and lung cancer are sorely needed.